SYNTHESIS OF NOVEL HETEROCYCLIC SYSTEM 4H-IMIDAZO [ 2,l -b] PYRIDO [2,3-el [I, 3,4] THIADIGZIM (Journal of Sciences, Islamic Republic of Iran)
Diazotization of 3-amino-2-cMoro pyridine (3) in the presence of dithizone (5) gave dphenyl-2-phenylazo-4H-pyrid[o3 ,2-e] [1,3,4] thiadiazine (6). Reaction of 2- chloro-3-nitropyridine (2, G=H) with (5) dfordd 4-phenyl -2-phenylazo -4Hpyrido [2,3-el [1,3,4] thiadiazine (7). Reduction of the latter with H gas in the presence of Raney nickel gave the corresponding amino derivative (12). One pot condensation and cyclization of the latter with phenacyl bromide gave a novel heterocyclic system (13).